ANTI-DIARRHEAL ACTIVITY OF AQUEOUS EXTRACT OF NAGASARI FLOWERS (Mesua ferrea L.) IN BALB/c MICE INDUCED BY Escherichia coli - Putu Monik Ananta Puspitarini; Iman Surya Pratama; Bambang Fajar Suryadi (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2019)
Nagasari (Mesua ferrea L.) is empirically used for curing diarrhea in Nusa Tenggara Barat Province. However, the safety and efficacy of nagasari have not been scientifically validated in animal model. This study evaluates the activity of nagasari flowers aqueous extract in BALB/c mice induced by Escherichia coli to determine the most effective dosage for anti-diarrheal effect. The aqueous extract of nagasari flowers ((0.4% (w/v), 0.8% (w/v), and 1.6% (w/v)) was given to 3 groups of mice whereas negative and positive control groups received aquadestilate and ciprofloxacin 130 mg/kgBW respectively orally once per day for 3 days. The frequency and consistency of feces were observed then the total colony of E. coli in feces was calculated using colony counter. Aqueous extract of nagasari flowers at concentration of 1.6% showed significant inhibitory activity against Escherichia coli compared to positive controls (diarrhea index of 0.425; p0.05 and total colony of E. coli in feces of 100.2; p0.05). This study provides scientific support for the traditional use of aqueous extract of nagasari flowers for the treatment of diarrheal diseases.